2021
DOI: 10.3390/en14020368
|View full text |Cite
|
Sign up to set email alerts
|

A Study of UVER in Santiago, Chile Based on Long-Term In Situ Measurements (Five Years) and Empirical Modelling

Abstract: Ultraviolet radiation is a highly energetic component of the solar spectrum that needs to be monitored because is harmful to life on Earth, especially in areas where the ozone layer has been depleted, like Chile. This work is the first to address the long-term (five-year) behaviour of ultraviolet erythemal radiation (UVER) in Santiago, Chile (33.5° S, 70.7° W, 500 m) using in situ measurements and empirical modelling. Observations indicate that to alert the people on the risks of UVER overexposure, it is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…This dispersion diagram (not show here) showed that hourly values of T78.6 ${T}_{78.6}$ and T1.5 ${T}_{1.5}$ have a linear distribution with a Pearson's coefficient of 0.99. Similar procedure has been used for developing empirical expressions to diagnosticate hourly values of diffuse and other components of solar radiation at the surface (Furlan et al., 2012; González‐Rodríguez et al., 2021).…”
Section: Measurements and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This dispersion diagram (not show here) showed that hourly values of T78.6 ${T}_{78.6}$ and T1.5 ${T}_{1.5}$ have a linear distribution with a Pearson's coefficient of 0.99. Similar procedure has been used for developing empirical expressions to diagnosticate hourly values of diffuse and other components of solar radiation at the surface (Furlan et al., 2012; González‐Rodríguez et al., 2021).…”
Section: Measurements and Datamentioning
confidence: 99%
“…The extrapolation is based on an empirical expression 𝐴𝐴 𝐴𝐴urban = 𝐴𝐴1.5 = 1.868 + 1.004 * 𝐴𝐴78.6 , obtained by fitting a first order polynomial through the dispersion diagram of the temperature measured in the surface at 1.5 m agl ( have a linear distribution with a Pearson's coefficient of 0.99. Similar procedure has been used for developing empirical expressions to diagnosticate hourly values of diffuse and other components of solar radiation at the surface (Furlan et al, 2012;González-Rodríguez et al, 2021).…”
Section: Uhi Intensitymentioning
confidence: 99%
“…-by employing parametrical models which are derived from spectral codes [6 -9], -using statistical models, such as polynomial regression analysis [10] or by using other types of models developed by statistical analysis of time series [11],…”
Section: Estimation Of Uv Radiation At Ground Levelmentioning
confidence: 99%
“…Some authors analyse how damage from sun exposure depends on cumulative daily doses and not only on UVI [10,34] and how exposure in the middle of the day to low levels of UV (UVI=2) poses a significant risk of erythema for people with lighter skin phototypes, even for a duration of 3 h [35].…”
Section: Uv Indexmentioning
confidence: 99%
“…Ultraviolet radiation (UV) represents a small fraction of total solar radiation (5-7%) [1]. It is a highly energetic component of the solar spectrum that must be monitored as it can be detrimental to life on Earth [2], becoming the main risk factor for human health among photo-biological factors [3]. The UV region of the solar spectrum spans wavelengths between 100 and 400 nm, and it is divided into three components, i.e., UVA, UVB, and UVC.…”
Section: Introductionmentioning
confidence: 99%